Simultaneous SAXS and SANS Analysis for the Detection of Toroidal Supramolecular Polymers Composed of Noncovalent Supermacrocycles in Solution. Issue 34 (7th July 2016) - Hollamby, Martin J.; Aratsu, Keisuke; Pauw, Brian R.; Rogers, Sarah E.; Smith, Andrew J.; Yamauchi, Mitsuaki; Lin, Xu; Yagai, Shiki
Abstract: Molecular self‐assembly primarily occurs in solution. To better understand this process, techniques capable of probing the solvated state are consequently required. Small‐angle scattering (SAS) has a proven ability to detect and characterize solutions, but it is rarely applied to more complex assembly shapes. Here, small‐angle X‐ray and neutron scattering are applied to observe toroidal assemblies in solution. Combined analysis confirms that the toroids have a core–shell structure, with a π‐conjugated core and an alkyl shell into which solvent penetrates. The dimensions determined by SAS agree well with those obtained by (dried‐state) atomic force microscopy. Increasing the number of naphthalene units in the molecular building block yields greater rigidity, as evidenced by a larger toroid and a reduction in solvent penetration into the shell. The detailed structural analysis demonstrates the applicability of SAS to monitor complex solution‐based self‐assembly. Abstract : Deconstructing donuts : Molecules comprising a barbituric acid hydrogen‐bonding unit, naphthalene body, and aliphatic tail self‐assemble in solution into toroids. Using small‐angle X‐ray and neutron scattering, with complementary spectroscopic and microscopic data, a core–shell structure is revealed. This demonstrates the applicability of small‐angle scattering analysis to complex solution‐based self‐assembled nanostructures.